The Effect of Service Quality, Image, and Brand Trust on Buying Interest in Shopee e-Commerce: Case Study on Students of the Faculty of Economics and Business, Makassar State University - Ramadhani, Putri; Musa, Muh. Ichwan; Burhanuddin; Aswar, Nurul Fadilah; Hasdiansa, Ilma Wulansari (International Humanity Advance, Business & Sciences, 2024)
This research is a quantitative study that aims to determine the effect of e-service quality, image and brand trust on buying interest (Case Study on Students of the Faculty of Economics and Business, Makassar State University). The population in this study were all active students of the Faculty of Economics and Business, Makassar State University class of 2020 using the sampling method obtained a sample of 100 respondents. The data collection technique used was a questionnaire. The analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS 20). The results of this study indicate that the e-service quality and brand image variables partially have a significant effect on purchase intention while the brand trust variable partially has no significant effect on purchase intention. Simultaneously, the variables of e-service quality, brand image and brand trust have a significant effect on purchase intention